Dynamic analysis and optimal control of a novel fractional-order 2I2SR rumor spreading model - Ye, Maolin; Li, Jiarong; Jiang, Haijun (Nonlinear Analysis: Modelling and Control, 2023)
In this paper, a novel fractional-order 2I2SR rumor spreading model is investigated. Firstly, the boundedness and uniqueness of solutions are proved. Then the next-generation matrix method is used to calculate the threshold. Furthermore, the stability of rumor-free/spreading equilibrium is discussed based on fractional-order Routh–Hurwitz stability criterion, Lyapunov function method, and invariance principle. Next, the necessary conditions for fractional optimal control are obtained. Finally, some numerical simulations are given to verify the results.